SYNTHESIS, IN SILICO CHARACTERIZATION AND EX VIVO EVALUATION OF THE NOVEL ORGANIC NITRATE NDIBP AS A POTENTIAL VASORELAXANT AGENT - MEDEIROS CAVALCANTI, AIRLLA LAANA DE; LINS ROCHA, PATRÍCIA KEYTTH; LUNA, ISADORA SILVA; BRANDÃO, MARIA CLÁUDIA RODRIGUES; DA TRINDADE, EMMELY OLIVEIRA; GUIMARÃES, GEOVANI PEREIRA; ATHAYDE-FILHO, PETRÔNIO FILGUEIRAS; MURATOV, EUGENE; KHAN, BARKAT; TULLIUS SCOTTI, MARCUS; et al. (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Objective: This study aimed to describe the synthesis and biological/pharmacokinetic potential of the 1,3-diisobutoxypropan-2-yl nitrate (NDIBP) using in silico and ex vivo approaches. Methods: The compound was characterized by Fourier-transform infrared spectroscopy and 1H and 13C- nuclear magnetic resonance spectra. NDIBP biological activity spectrum was obtained by Prediction of Activity Spectra for Substances (PASS). The pharmacological effect was validated in ex vivo studies using mesenteric artery. Drug-like properties and Absorption Distribution Metabolism Excretion and Toxicity (ADMET) studies were carried out by pkCSM (Predicting Small-Molecule Pharmacokinetic Properties Using Graph-Based Signatures) software. Results: PASS prediction indicated NDIBP as nitric oxide (NO) donor with vasodilator effect. Ex vivo studies validated PASS analysis and showed the NDIBP vasorelaxant activity in mesenteric arteries. Physicochemical parameters and ADMET prediction suggested that NDIBP is a drug-like molecule with a good theoretical oral bioavailability, good absorption in the gastrointestinal tract, and a low distribution in the tissues. Conclusion: All the data indicated that NDIBP possesses biological activities and drug-like properties to be considered as a vasorelaxant agent and a good candidate for further investigation in the treatment of arterial hypertension and drug development studies.